METHODS USED IN TEACHING ENGLISH TO STUDENTS - Ozoda Eshkobilova; Sevinch Kholmatova (TADQIQOTLAR.UZ, 2024)
The methods used in teaching English to students have evolved significantly over time, reflecting changes in educational theories, technological advancements, and shifts in pedagogical priorities. Early approaches, such as the Grammar-Translation Method and the Direct Method, emphasized rote memorization and direct immersion in the target language. Later methods, like the Audio-Lingual Method, focused on repetitive drills and language patterns, while Communicative Language Teaching (CLT) emerged as a response to emphasize real-world communication, fluency, and interaction over strict grammatical accuracy. More recent approaches, such as Task- Based Language Teaching (TBLT) and Content and Language Integrated Learning (CLIL), integrate language learning with practical tasks and subject content, fostering a more dynamic, student-centered environment. Other methods, like the Silent Way and Total Physical Response (TPR), prioritize learner autonomy and kinesthetic learning, offering diverse pathways for engaging students in the language acquisition process. The choice of method depends on the learners’ needs, context, and learning objectives, with many educators blending approaches to create a balanced, effective curriculum. This diversity in teaching methods highlights the complexity of language education and the importance of adapting strategies to ensure learners’ comprehensive language development.